2013
DOI: 10.1002/chem.201203215
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Gradient Surfaces by Using a Simple Chemical Reaction and Investigation of Cell Adhesion on a Two‐Component Gradient

Abstract: This article describes a simple method for the generation of multicomponent gradient surfaces on self-assembled monolayers (SAMs) on gold in a precise and predictable manner, by harnessing a chemical reaction on the monolayer, and their applications. A quinone derivative on a monolayer was converted to an amine through spontaneous intramolecular cyclization following first-order reaction kinetics. An amine gradient on the surface on a scale of centimeters was realized by modulating the exposure time of the qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…This is in agreement with observations that have been made on other substrates. Lee et al have reported similar findings when studying 3T3 cell adhesion on mixed RGD/PHSRN presenting gold substrates [27]. When studying osteoblast differentiation in mixed hydrogels generated from RGD-and PHSRN-modified alginates, Nakaoka et al found qualitative enhancement of the differentiation levels of these cells when they were encapsulated in gels containing 50 or 67% of the RGD-alginate [28].…”
Section: Cell Adhesion and Proliferation On Rgd/phsrn Co-presenting Pmentioning
confidence: 78%
See 1 more Smart Citation
“…This is in agreement with observations that have been made on other substrates. Lee et al have reported similar findings when studying 3T3 cell adhesion on mixed RGD/PHSRN presenting gold substrates [27]. When studying osteoblast differentiation in mixed hydrogels generated from RGD-and PHSRN-modified alginates, Nakaoka et al found qualitative enhancement of the differentiation levels of these cells when they were encapsulated in gels containing 50 or 67% of the RGD-alginate [28].…”
Section: Cell Adhesion and Proliferation On Rgd/phsrn Co-presenting Pmentioning
confidence: 78%
“…Chen et al, for example, investigated RGD/ PHSRN co-presentation on titanium surfaces and found that osteoblast adhesion, proliferation and differentiation on surfaces that presented equimolar amounts of both peptides were enhanced as compared to surfaces that only presented one of the ligands [26]. Yeo et al have compared the adhesion of NIH3T3 fibroblasts on gold surfaces that were modified with the RGD/PHSRN peptides grafted in molar ratios of 9/1, 5/5 and 1/4 and found that equimolar presentation of the two ligands resulted in the highest cell densities [27]. Similar findings were reported for peptide-modified alginate hydrogels that were used as 2D and 3D substrates for osteoblasts [28].…”
Section: Introductionmentioning
confidence: 96%
“…A variation of this method has also recently been described that involves the electrochemical desorption/readsorption of surface modifiers while withdrawing the substrate from solution [13]. Other approaches to the formation of multi-component gradients include gradually exposing a suitable substrate to a modifying solution followed by full immersion [14][15][16], creation of a gradient monolayer via microfluidic lithography followed by backfilling [17], the use of a photo-mask followed by electrochemical oxidation and selective immobilization [18], modulating the exposure time of a self-assembled monolayer on gold to a reducing agent [19] and cross diffusion of different organothiols through a sephadex gel on a gold slide [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A major advantage is the abundance of thiols in proteins or peptides and the easy introduction of cysteines in tailor-made biomolecules. Applications of thiol mediated modification of gold are predominately focused on analytical investigations (Huang et al, 2009;Lee et al, 2013a;Migliorini et al, 2014). Interestingly, thiols were used for the immobilization of multifunctional motifs to titaniumsurfaces as well (Mas-Moruno et al, 2013;Mas-Moruno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%